2014
DOI: 10.1016/j.buildenv.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of a hemp concrete wall: Impact of thickness and coating

Abstract: In a context of sustainable development and energy sparing, a life cycle assessment (LCA) may be useful to make good choices. Thus, this study concerns the LCA of an environmentally friendly material used for building construction, hemp concrete. The functional unit is first defined per square such that the wall may provide the function of bearing wall meter and its thermal performance is described by a thermal resistance of 2.78 m².K/W. The results then showed that the production phase of raw materials is mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(106 citation statements)
references
References 14 publications
2
101
0
3
Order By: Relevance
“…The aim of the present study is to compare the moisture buffer values of vapour-open wall assemblies containing hemplime and inner linings and surface treatments with that of the exposed hemp-lime. The Nordtest [9] protocol is followed to determine the moisture buffer values of the assembly. The experiments described in this article are part of the experiments being carried out in the EPSRC-funded HIVE building situated in the Building Research Park at Wroughton, UK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the present study is to compare the moisture buffer values of vapour-open wall assemblies containing hemplime and inner linings and surface treatments with that of the exposed hemp-lime. The Nordtest [9] protocol is followed to determine the moisture buffer values of the assembly. The experiments described in this article are part of the experiments being carried out in the EPSRC-funded HIVE building situated in the Building Research Park at Wroughton, UK.…”
Section: Introductionmentioning
confidence: 99%
“…Hemp shiv comes from renewable sources and lime is a flexible, reusable and breathable material with significantly lower embodied energy than conventional masonry materials [4]. Because of its low compressive strength [5e8], hemplime is typically used as an insulating infill material between structural framework [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Rahim's research [5] composites porosity was comparable -hemp composite with apparent density of 478 kg/m 3 indicated total porosity equal to 76.4% and rape straw composite with apparent density of 487 kg/m 3 indicated total porosity equal to 75.1% . Other research [8] has presented that composite revealed total porosity of 79% with the apparent densities of 430-460 kg/m 3 .…”
Section: Apparent Density Specific Density and Total Porositymentioning
confidence: 99%
“…With respect to Cole who stated the scarcity to find similar built projects can show the capability of expanding our environmental performance targets (Cole, 2012;Waldron, Cayuela, & Miller, 2013;Wolpensinger & nachhaltiges Bauen, 2016). This study is in line environmental assessments made for plant based construction materials (Van der Lugt, 2008;Prétot, Collet, & Garnier, 2014;Ip & Miller, 2012;Wolpensinger & nachhaltiges Bauen, 2016;Waugh, Wells, & Lindegar, 2010). Despite the small sample of case studies, the author tried to go into buildings with a well-defined focus and to collect specific building performance data systematically.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%